Radiation retinopathy following episcleral brachytherapy for intraocular tumors: Current treatment options - Mularska, Weronika; Chicheł, Adam; Rospond-Kubiak, Iwona (Journal of Contemporary Brachytherapy, 2023)
Radiation retinopathy (RR) and radiation maculopathy (RM) can occur as a result of uveal melanoma radiation treatment and after irradiation of other head and neck extraocular tumors, even with precise targeting techniques, such as stereotactic or proton beam radiotherapy. This review provides an overview of the current understanding of potential radiation damage to ocular tissues, and how recent developments in ophthalmic multimodal imaging techniques and treatment modalities have improved managing options. Several treatment strategies have been employed so far for the management of RR, including laser photocoagulation, intravitreal injections of anti-vascular endothelial growth factor (VEGF) agents or glucocorticosteroids and surgery. The use of intravitreal anti-VEGFs or dexamethasone implants have significantly altered the final visual outcome for uveal melanoma patients. As a prophylaxis, a few different strategies were proposed, but still there is a lack of large randomized clinical trials supporting these approaches and clear clinical guidelines for daily practice. Early detection and proper treatment are crucial in preventing or reducing vision loss, and improving patients’ quality of life. Close monitoring and timely intervention are essential for successful management.